2021
DOI: 10.3897/zookeys.1049.66645
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular data on tadpoles of the westernmost Himalayan spiny frog Allopaa hazarensis (Dubois & Khan, 1979)

Abstract: Little is known about the life history, ecology, and distribution of the genus Allopaa (Dicroglossidae) and far less recent data are available about the larvae of this taxon. Here, we provide data on the larval stage of Allopaa hazarensis (Dubois & Khan, 1979) from northern Pakistan based on the examination of three tadpoles. Specimens were obtained from two sites in Buner, Khyber Pakhtunkhwa province, Pakistan. Morphological and genetic analysis (mtDNA and nDNA) confirmed the identity of the tadpoles … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 11 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…Appendices 5 and 6), with genetic distance of 2.1% between N. vicina and A. hazarensis (Table S5). Hofmann et al (2021) also reported this paraphyletic relationship of Allopaa with respect to genus Nanorana.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…Appendices 5 and 6), with genetic distance of 2.1% between N. vicina and A. hazarensis (Table S5). Hofmann et al (2021) also reported this paraphyletic relationship of Allopaa with respect to genus Nanorana.…”
Section: Discussionmentioning
confidence: 68%
“…Hofmann et al. ( 2021 ) also reported this paraphyletic relationship of Allopaa with respect to genus Nanorana .…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations